Kidnapped. The Adventures of David Balfour in the Year 1751 - Stevenson, Robert Louis (Oxford Bookworms, 2008)
A level 3 Oxford Bookworms Library graded reader. Retold for Learners of English by Clare West. ‘I ran to the side of the ship. “Help, help! Murder!” I screamed, and my uncle slowly turned to look at me. I did not see any more. Already strong hands were pulling me away. Then something hit my head; I saw a great flash of fire, and fell to the ground . . .’ And so begin David Balfour’s adventures. He is kidnapped, taken to sea, and meets many dangers. He also meets a friend, Alan Breck. But Alan is in danger himself, on the run from the English army across the wild Highlands of Scotland . . .